425 - Incorporating young children into family caregiving for people with dementia in Taiwan. (October 2021) - Kuo, Ching-Yi; Chen, Shu-Chuan
Abstract : Background: Positive attitudes and appropriate knowledge about dementia are essential for the provision of suitable dementia care. Children as future voters may take on a critical role to increase community awareness and knowledge about dementia. Guided by Chinese filial piety cultural virtues, Taiwanese children are taught to respect and care for family seniors and extend this respect to other seniors. Accordingly, young children are considered part of family dementia caregiving system, despite children rarely assume formal caregiver role and not directly provide care work. However, Taiwanese children may possess stigmatized attitudes toward dementia due to a lack of proper dementia knowledge. Research Objective: This study aims to survey Taiwanese children age 9-11 years old attitudes and knowledge to the concepts of dementia. Methods: A total of 312 Taiwanese children from 8 elementary schools in the south Taiwan, aged 9-11 years old, were surveyed to assess their knowledge and attitudes toward dementia. Participants completed The Kids Insight into Dementia (KIDS), which is a 5-scale questionnaire containing three factors, "Personhood", "Stigma", and "Dementia Understanding". The data was analyzed using quantitative method. Results: The results show that Taiwanese children are unfamiliar with dementia as related to brain disease (M= 3.94, SD=2.91), Taiwanese children are unfamiliar about nursing home provision of care (M=3.97, SD=2.17), Taiwanese children do not know the course of dementia disease (M=3.34, SD-1.39). Participants scored high on the question of "people with dementia have hobbies and interests" (M=4.15, SD=1.22); Participants reported that they agreed less often with stigma attached to the people with dementia, including items of "I would feel a bit scared if I met someone dementia in the street" (M=2.70, SD=1.79), "people with dementia can be creepy" (M=2.18, SD=1.71), "It would be annoying of frustrating to spend time with someone with dementia" (M=2.15, SD=1.17), "It is unlikely that I would meet someone with dementia" (M=2.36, SD=1.27). Conclusions: Our findings suggest that Taiwanese children may express less stigmatized attitudes toward people with dementia and yet they report less understanding of concepts of personhood of people with dementia. Therefore, dementia education is necessary to increase dementia knowledge among school age children in Taiwan.